Impact of the Covid-19 Pandemic on Mental Health of Children, Adolescents, and Young Adults. Issue 4 (July 2021) - Beal, Judy A.
Abstract : The COVID-19 pandemic has caused much stress and anxiety among children, adolescents, and young adults in the United States. Our pediatric nursing expert, Dr. Beal, reviews the latest literature and offers suggestions that nurses can use in clinical pediatric care.